Decompressive craniectomy for malignant middle cerebral artery infarction: Impact on mortality and functional outcome - Raffiq, Mohammad Azman Mohammed (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Malignant middle cerebral artery (MCA) infarction is a devastating clinical entity affecting about 10% of stroke patients. Decompressive craniectomy has been found to reduce mortality rates and improve outcome in patients. METHODS: A retrospective case review study was conducted to compare patients treated with medical therapy and decompressive surgery for malignant MCA infarction in Hospital Kuala Lumpur over a period of 5 years (from January 2007 to December 2012). A total of 125 patients were included in this study; 90 (72%) patients were treated with surgery, while 35 (28%) patients were treated with medical therapy. Outcome was assessed in terms of mortality rate at 30 days, Glasgow Outcome Score (GOS) on discharge, and modified Rankin scale (mRS) at 3 and 6 months. RESULTS: Decompressive craniectomy resulted in a significant reduction in mortality rate at 30 days (P < 0.05) and favorable GOS outcome at discharge (P < 0.05). Good functional outcome based on mRS was seen in 48.9% of patients at 3 months and in 64.4% of patients at 6 months (P < 0.05). Factors associated with good outcome include infarct volume of less than 250 ml, midline shift of less than 10 mm, absence of additional vascular territory involvement, good preoperative Glasgow Coma Scale (GCS) score, and early surgical intervention (within 24 h) (P < 0.05). Age and dominant hemisphere infarction had no significant association with functional outcome. CONCLUSION: Decompressive craniectomy achieves good functional outcome in, young patients with good preoperative GCS score and favorable radiological findings treated with surgery within 24 h of ictus.